Identifikasi Kendala Yang Dialami Guru Dalam Menyusun Alur Tujuan Pembelajaran - Agus Prasetyo Utomo; Wahju Dyah Laksmi Wardhani; Fatchurhohman Fatchurhohman (Journal of Community Development, 2024)
The implementation of the Independent Curriculum (IKM) at the basic education level is divided into three stages of learning outcomes, namely phase A, phase B, and phase C. The flow of learning objectives (ATP) is a new way as a "syllabus", namely for planning, setting learning and assessment in outline according to the characteristics and competencies developed by each subject at the end of each phase. This form of service is carried out in collaboration with SD Muhammadiyah Kaliwates (SD HAMKA), which is one of the educational business charities of Muhammadiyah which has only been established for 3 years in Jember. By using participatory assistance methods, implementation is carried out in 4 stages, namely needs mapping, pumped group discussions with experts, mentoring and evaluation. During the pumped group discussion, it was known that there were obstacles in the implementation of activities. First, the implementation of IKM in classes 1 and 2 only, while class 3 still uses K13. The 3rd grade teacher hasn't understood yet. Second, SD HAMKA has not appointed grade 4 teachers as partners for grade 3 teachers in formulating ATP in phase B. This makes it difficult for grade 3 teachers to develop ATP. The third obstacle, teachers experience limited time and means to complete ATP development.